The predictive role of self‐compassion in cancer patients' symptoms of depression, anxiety, and fatigue: A longitudinal study. Issue 9 (21st July 2019) - Zhu, Lei; Yao, Juntao; Wang, Jun; Wu, Liyang; Gao, Yuhan; Xie, Juan; Liu, Ailan; Ranchor, Adelita V.; Schroevers, Maya J.
Abstract: Objective Self‐compassion is consistently found to be related to better psychological outcomes. As most studies were cross‐sectional, little is known about the predictive role of self‐compassion for future psychological outcomes. This longitudinal study in cancer patients investigated the predictive role of self‐compassion at the time of cancer diagnosis for the course of symptoms of depression, anxiety, and fatigue in the period of receiving cancer treatment. Methods: This longitudinal study was conducted at the Shaanxi Provincial Tumour Hospital in Xi'an, China. A total of 153 heterogeneous cancer patients were assessed within 1 week after cancer diagnosis (T1) as well as at the start (T2) and the end (T3) of medical treatment. Hierarchical linear regression analyses were conducted to examine the research questions. Results: Cross‐sectional regression analyses at T1 showed that a self‐compassion total score and negative self‐compassion (and to a lesser extent positive self‐compassion) were significantly related to symptoms of depression, anxiety, and fatigue. When controlling for symptoms at T1, positive self‐compassion significantly predicted all three outcomes at T3. A self‐compassion total score only predicted symptoms of anxiety at T2, controlling for T1 symptoms. In contrast, we found no significant predictive value of negative self‐compassion. Conclusions: This study suggests that the positive aspects of self‐compassion are beneficial for cancer patients for their future functioning, in terms of fewer symptoms of depression, anxiety, and fatigue over time. Future interventions should test how and to what extent self‐compassion can be cultivated and whether increases in self‐compassion are associated with better outcomes.